The Geometry Transformation Concepts in Bead Craft Motifs by the Kenyah Dayak Tribe - Yahya, Muhammad Hafizh Naufal; Haeruddin, Haeruddin; Muhtadin, Achmad; Rizki, Nanda Arista (Ethnomathematics Journal, 2023)
When studying mathematics, many students consider mathematics to be a difficult subject because they see it as a close system that prioritizes standards of rigor, speed, and memory. Conventional learning methods might make students bored. Various model is needed to overcome this. One of which is the culture associated with learning mathematics, known as ethnomathematics. The purpose of this study was to explore the bead crafts of the Kenyah Dayak tribe, located in Kalimantan, Indonesia, that develop heritage motifs attributed to the concept of geometric transformations on rotation and dilatation. This type of research was qualitative research involving observation, interviews, and documentation. The subject of this study was bead craft in the local area and the object of this study was the concept of geometric transformation on rotation and dilatation that exists in the craft motifs of the beads made. The data obtained in this study provides insights into the various cultural objects that can be used for triggering mathematics thinking. Through this resource, students may understand geometric concepts such as rotation and dilation, applicable to the real context of their daily life.